PENGARUH LAMA WAKTU PERENDAMAN RESIN AKRILIK DI DALAM EKSTRAK DAUN KEMANGI (Ocimum basilicum) TERHADAP PERTUMBUHAN Candida albicans - Ismi Dea Nurintan (FKG 16 UMY 158, 2016)
Denture’s hygiene which is not taken care of can lead to denture stomatitis that is caused by plaque accumulation and bacterial or fungal colonization. Fungal colonization that is often found is Candida albicans. Denture cleanser that is characterized as nontoxic, antifungal, antibacterial, and can work in short period is required. Basil leaf contains atsiri oil, flavonoid, saponin and tannin which works as antifungal and antibacterial. The aim of this study was to find out the influence of soaking period of acrylic resin in basil leaf extract towards the growth of Candida albicans. Fifteen plates of acrylic resin is divided into 3 groups. Group 1 was soaked into 80% of basil leaf extract concentration for 4 hours, group 2 was soaked for 6 hours, and group 3 was soaked for 8 hours. The result of one-way ANOVA test showed that there was a significant difference p< 0,05. Group with 8 hours of soaking period is the most effective in inhibiting the growth of Candida albicans. Keywords: acrylic resin, candida albicans, ocimum basilicum, soaking period